2011
DOI: 10.1016/j.jacc.2010.11.017
|View full text |Cite
|
Sign up to set email alerts
|

Effects of n-3 Polyunsaturated Fatty Acids on Left Ventricular Function and Functional Capacity in Patients With Dilated Cardiomyopathy

Abstract: In patients with NICM and minimal symptoms in response to evidence-based medical therapy, n-3 PUFAs treatment increases LV systolic function and functional capacity and may reduce hospitalizations for HF. Given these promising results, larger studies are in order to confirm our findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
137
1
11

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 185 publications
(151 citation statements)
references
References 19 publications
2
137
1
11
Order By: Relevance
“…17 Controlled trials in heart failure patients suggest that omega-3 supplementation may improve LV systolic function. 16,50 These prior studies were limited by modest samples, referral bias, a select focus on people with prevalent disease or use of less robust measures of fish oil intake.…”
Section: Omega-3 Fatty Acids Cardiac Structure and Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…17 Controlled trials in heart failure patients suggest that omega-3 supplementation may improve LV systolic function. 16,50 These prior studies were limited by modest samples, referral bias, a select focus on people with prevalent disease or use of less robust measures of fish oil intake.…”
Section: Omega-3 Fatty Acids Cardiac Structure and Functionmentioning
confidence: 99%
“…Omega-3 fatty acids also have been related to favorable effects on cardiac function and geometry in experimental models and smaller epidemiological studies, 13,14 and therapeutic administration has demonstrated beneficial effects in the treatment of chronic congestive heart failure in some studies. 15,16 Other PUFAs also have been associated with cardiovascular risk. In particular, the intake of omega-6 fatty acids (primarily linoleic acid (18:2ω-6)) has been associated with reduced cardiovascular risk and with a lower prevalence of future left ventricular (LV) hypertrophy in some studies, 17,18 but the published literature is not conclusive.…”
Section: Introductionmentioning
confidence: 99%
“…A recent randomized controlled trial conducted by Nodari et al [48] evaluated 133 patients with chronic HF secondary to non-ischemic cardiomyopathy and demonstrated significant improvements in many HF and major CV parameters at 12 month follow up in the subjects who received 2 g/ day omega-3 fatty acid supplementation versus placebo Left ventricular ejection fraction in the omega-3 arm was increased by 10.4% compared to a decrease of 5.0% in the placebo arm (p<0.001). Significant improvements in exercise capacity, New York Heart Association functional class, re-hospitalization rates, and inflammatory cytokines were also seen with omega-3 PUFA [48].…”
Section: Evidence In CV Diseasementioning
confidence: 99%
“…To verify these effects, we enrolled 133 patients with chronic HF due to nonischemic dilated cardiomyopathy, EF\45%, stable clinical conditions on evidence-based medical treatment at maximum tolerated target doses for at least 6 months, into a double-blind, placebo-controlled, two-arm study [76]. Participants were randomly allocated to active treatment (1.0 g gelatin capsules containing 850-882 mg of eicosapentaenoic (EPA) and docosahexaenoic (DHA) ethyl esters in the average ratio EPA/DHA of 0.9:1.5) or to placebo (1.0 g gelatin capsules containing olive oil).…”
Section: Antiarrhythmic Effectsmentioning
confidence: 99%
“…DHA is more represented than EPA in myocyte membrane and its administration (alone or in Fig. 1 Variations of the EF in the two study groups (from Nodari [76])…”
Section: Dose and Optimal Ratio Of Dha/epamentioning
confidence: 99%